ضمانات المساءلة التأديبية للموظف العام - عبد الغاني براهمية (My University, 2020)
Summary: Public servants play an important role in establishing the principle of discipline that must be available to enable management to fulfil its role in the public interest. It serves as a means of punishing public servants for proven irregularities and professional errors in order to confront delinquent behaviour that constitutes a departure from the requirements of the functional duty and a threat to the principle of the proper functioning of public utilities on a regular basis. If the principle of the effectiveness of disciplinary punishment is directed towards strengthening the powers of the disciplinary authority in the interest of the administrative organ of the State, it should not be at the expense of the guarantees of employees who practise discipline in the face of them rights ", where such safeguards constitute rights of the staff member that correspond to the broad powers of management and hence require, The disciplinary authority must balance the principles of effectiveness and security without prejudice or exclusion. This study showed that management authority has extensive disciplinary powers. act as an adversary by specifying the elements and descriptions of professional error committed by the public official, It also exercises the role of judgement by imposing punishment. In view of these broad powers, the staff legislation provides a number of guarantees that are necessary to achieve fair accountability and reassurance for the public official. and to reduce the wide range of management practices that may drag them towards abuse of power. This study has demonstrated the inadequacy of the procedures contained in these safeguards, And the lack of clarity of some of them, as also showed the tendency of Algerian legislator in many times to overcome the element of effectiveness over the element of guarantee in discipline. ,,,,,,,,,,,,,,,,,,,,,,, ﻣﻠﺧص : ﻟﻠﺗﺄدﯾب ﻓﻲ اﻟوظﯾﻔﺔ اﻟﻌﺎﻣﺔ دور ﻫﺎم ﻓﻲ إرﺳﺎء ﻣﺑدأ اﻻﻧﺿﺑﺎط اﻟواﺟب ﺗواﻓرﻩ ﻟﺗﻣﻛﯾن اﻹدارة ﻣن اﻻﺿطﻼع ﺑﻣﺎ ﯾﻧﺎط ﺑﻬﺎ ﻣن دور ﻟﺗﺣﻘﯾق اﻟﺻﺎﻟﺢ اﻟﻌﺎم، ﻓﻬو ﺑﻣﺛﺎﺑﺔ وﺳﯾﻠﺔ ﻟﻌﻘﺎب اﻟﻣوظف اﻟﻌﻣوﻣﻲ ﺟزاء ﻟﻣﺎ ﺛﺑت ﻓﻲ ﺣﻘﻪ ﻣن ﻣﺧﺎﻟﻔﺎت وأﺧطﺎء ﻣﻬﻧﯾﺔ ﺑﻐرض ﻣواﺟﻬﺔ ﺳﻠوك ﻣﻧﺣرف ﯾﺷﻛل ﺧروﺟﺎ ﻋﻠﻰ ﻣﻘﺗﺿﯾﺎت اﻟواﺟب اﻟوظﯾﻔﻲ وﺗﻬدﯾدا ﻟﻣﺑدأ ﺣﺳن ﺳﯾر اﻟﻣراﻓق اﻟﻌﺎﻣﺔ ﺑﺎﻧﺗظﺎم واطراد . ذا ﻛﺎن ﯾﺗﺟﻪ ﻣﺑدأ ﻓﺎﻋﻠﯾﺔ اﻟﻌﻘوﺑﺔ اﻟﺗﺄدﯾﺑﯾﺔ ﻧﺣو ﺗﻘوﯾﺔ ﺳﻠطﺎت اﻟﻬﯾﺋﺔ اﻟﺗﺄدﯾﺑﯾﺔ ﺗﺣﻘﯾﻘﺎ ﻟﻣﺻﻠﺣﺔ اﻟﺟﻬﺎز اﻹداري ﻓﻲ اﻟدوﻟﺔ ﻓﺈن ذﻟك ﯾﻧﺑﻐﻲ أﻻ ﯾﻛون ﻋﻠﻰ ﺣﺳﺎب ﺿﻣﺎﻧﺎت اﻟﻣوظﻔﯾن اﻟذﯾن ﯾﻣﺎرس اﻟﺗﺄدﯾب ﻓﻲ ﻣواﺟﻬﺗﻬم ، ﺣﯾث ﺗﺷﻛل ﺗﻠك اﻟﺿمانات ﺣﻘوﻗﺎ ﻟﻠﻣوظف ﺗﻘﺎﺑل ﺳﻠطﺎت اﻹدارة اﻟواﺳﻌﺔ وﻣن ﺛم ﯾﺗﻌﯾن ،ﻋﻠﻰ اﻟﺳﻠطﺔ اﻟﺗﺄدﯾﺑﯾﺔ أن ﺗوازن ﻣﺎﺑﯾن ﻣﺑدأي اﻟﻔﻌﺎﻟﯾﺔ واﻟﺿﻣﺎن دون اﻧﺣﯾﺎز أو ﺗﻔرﯾط ﻓﻛﻼﻫﻣﺎ ﺟدﯾر ﺑﺎﻟرﻋﺎﯾﺔ . وﻟﻘد أظﻬرت ﻫذﻩ اﻟدراﺳﺔ ﺗﻣﺗﻊ اﻟﺳﻠطﺔ اﻹدارﯾﺔ ﺑﺻﻼﺣﯾﺎت واﺳﻌﺔ ﻓﻲ ﻣﺟﺎل اﻟﺗﺄدﯾب، ﻓﻬﻲ ﺗﻘوم ﺑدور اﻟﺧﺻم ﺑﺗﺣدﯾدﻫﺎ ﻋﻧﺎﺻر وأوﺻﺎف اﻟﺧطﺄ اﻟﻣﻬﻧﻲ اﻟﻣﻘﺗرف ﻣن طرف اﻟﻣوظف اﻟﻌﻣوﻣﻲ، ﻛﻣﺎ ﺗﻣﺎرس دور اﻟﺣﻛم ﺑﺗوﻗﯾﻌﻬﺎ ﻟﻠﻌﻘوﺑﺔ .إزاء ﻫذﻩ اﻟﺻﻼﺣﯾﺎت اﻟواﺳﻌﺔ ﻧﺻت اﻟﺗﺷرﯾﻌﺎت اﻟوظﯾﻔﯾﺔ ﻋﻠﻰ ﻋدد ﻣن اﻟﺿﻣﺎﻧﺎت اﻟﺗﻲ ﻻ ﺑد ﻣﻧﻬﺎ ﻟﺗﺣﻘﯾق ﻣﺳﺎءﻟﺔ ﺗﺄدﯾﺑﻪ ﻋﺎدﻟﺔ ﻟﻠﻣوظف اﻟﻌﺎم وﺑث اﻟطﻣﺄﻧﯾﻧﺔ ﻓﻲ ﻧﻔﺳﻪ، وﻟﻠﺣد ﻣن اﻟﻣﺟﺎل اﻟواﺳﻊ ﻟﻣﻣﺎرﺳﺎت اﻹدارة اﻟﺗﻲ ﻗد ﺗﺟرﻫﺎ ﻧﺣو اﻟﺗﻌﺳف ﻓﻲ اﺳﺗﻌﻣﺎل اﻟﺳﻠطﺔ .واﺗﺿﺢ ﺟﻠﯾﺎ ﻣن ﺧﻼل ﻫذﻩ اﻟدراﺳﺔ ﻋدم ﻛﻔﺎﯾﺔ اﻹﺟراءات اﻟﻣﺗﺿﻣﻧﺔ ﻟﻬذﻩ اﻟﺿﻣﺎﻧﺎت، و ﻋدم وﺿوح اﻟﺑﻌض ﻣﻧﻬﺎ، ﻛﻣﺎ ﺑﯾﻧت أﯾﺿﺎ ﻣﯾل اﻟﻣﺷرع اﻟﺟزاﺋري ﻓﻲ ﻛﺛﯾر ﻣن اﻷﺣﯾﺎن إﻟﻰ ﺗﻐﻠﯾب ﻋﻧﺻر اﻟﻔﻌﺎﻟﯾﺔ ﻋﻠﻰ ﻋﻧﺻر اﻟﺿﻣﺎن ﻓﻲ اﻟﺗﺄدﯾب . ,,,,,,,,,,,,,,,,,,,,,,,,,,,, Résumé : Les fonctionnaires jouent un rôle important dans l’établissement du principe de discipline qui doit être disponible pour permettre à la direction de jouer son rôle dans l’intérêt public. Il sert de moyen de punir les fonctionnaires pour les irrégularités avérées et les erreurs professionnelles afin de faire face à un comportement délinquant qui constitue une dérogation aux exigences du devoir fonctionnel et une menace pour le principe du bon fonctionnement du public services publics sur une base régulière. Si le principe de l’efficacité de la sanction disciplinaire vise à renforcer les pouvoirs de l’autorité disciplinaire dans l’intérêt de l’organe administratif de l’État, il ne devrait pas être aux dépens des garanties des employés qui pratiquent la discipline face à leurs droits ", lorsque de telles garanties constituent des droits du membre du personnel qui correspondent aux vastes pouvoirs de la direction et exigent donc, l’autorité disciplinaire doit équilibrer les principes d’efficacité et de sécurité sans préjudice ni exclusion. Cette étude a montré que l’autorité de gestion dispose de vastes pouvoirs disciplinaires. agir comme un adversaire en spécifiant les éléments et les descriptions de l’erreur professionnelle commise par le fonctionnaire, Il exerce également le rôle de jugement en imposant des sanctions. Compte tenu de ces vastes pouvoirs, la législation sur le personnel prévoit un certain nombre de garanties qui sont nécessaires pour assurer une reddition de comptes équitable et rassurer le fonctionnaire. et de réduire le large éventail de pratiques de gestion qui peuvent les entraîner vers l’abus de pouvoir. Cette étude a démontré l’insuffisance des procédures contenues dans ces garanties, et le manque de clarté de certains d’entre eux, ainsi que la tendance du législateur algérien à maintes reprises à surmonter l’élément d’efficacité sur l’élément de garantie dans la discipline.